A network physiology approach to oxygen saturation variability during normobaric hypoxia. Issue 1 (20th July 2020) - Jiang, Yuji; Costello, Joseph T.; Williams, Thomas B.; Panyapiean, Nawamin; Bhogal, Amar S.; Tipton, Michael J.; Corbett, Jo; Mani, Ali R.
Abstract : New Findings: What is the central question of this study? What is the physiological interpretation of S p O 2 fluctuations observed during normobaric hypoxia in healthy individuals? What is the main finding and its importance? There is a significant flow of information between S p O 2 and other cardio‐respiratory time series during graded hypoxia. Analysis of the pattern of S p O 2 variations has potential for non‐invasive assessment of the engagement of respiratory control system in health and disease. Abstract: Peripheral capillary oxygen saturation ( S p O 2 ) exhibits a complex pattern of fluctuations during hypoxia. The physiological interpretation of S p O 2 variability is not well understood. In this study, we tested the hypothesis that S p O 2 fluctuation carries information about integrated cardio‐respiratory control in healthy individuals using a network physiology approach. We explored the use of transfer entropy in order to compute the flow of information between cardio‐respiratory signals during hypoxia. Twelve healthy males (mean (SD) age 22 (4) years) were exposed to four simulated environments (fraction of inspired oxygen ( F I O 2 ): 0.12, 0.145, 0.17, and 0.2093) for 45 min, in a single blind randomized controlled design. The flow of information between different physiological parameters ( S p O 2, respiratory frequency, tidal volume, minute ventilation, heart rate, end‐tidal pressure of O2 and CO2 ) were analysed using transfer entropy. Normobaric hypoxia was associated with a significant increase in entropy of the S p O 2 time series. The transfer entropy analysis showed that, particularly at F I O 2 0.145 and 0.12, the flow of information between S p O 2 and other physiological variables exhibits a bidirectional relationship. While reciprocal interactions were observed between different cardio‐respiratory parameters during hypoxia, S p O 2 remained the main hub of this network. S p O 2 fluctuations during graded hypoxia exposure carry information about cardio‐respiratory control. Therefore, S p O 2 entropy analysis has the potential for non‐invasive assessment of the functional connectivity of respiratory control system in various healthcare settings. Abstract :